The spontaneous room temperature reduction of HAuCl4 in ethylene glycol in the presence of ZnO: A simple strategy to obtain stable Au/ZnO nanostructures exhibiting strong surface plasmon resonance and efficient electron storage properties - Aguirre, Matías Ezequiel (2015)
The room temperature spontaneous reduction of HAuCl4 in ethylene glycol in the presence of pre-formed ZnO nanoparticles is investigated by UV-vis spectroscopy. Analysis by HRTEM demonstrated that the synthesized nanostructures consist of small ZnO nanoparticles (5.0 nm) in contact with bigger (15 nm) spherical Au nanoparticles. The electronic communication between Au and ZnO blocks is confirmed by UV excitation of the colloid. These experiments indicate that ZnO nanoparticles efficiently transfer the electrons to Au nanoparticles in contact, inducing a 15 nm blue shift in the plasmon band. Titration experiments using the methylviologen couple (MV2+/MV+) are presented and analyzed to quantify the enhancement in the electron storage capability in the new nanostructure and the negative shift in the Fermi level caused by the Au loading in ZnO.